2015
DOI: 10.3390/molecules20034655
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Olive Oil Phenolic Compounds in the Prevention of Neurodegenerative Diseases

Abstract: Adherence to the Mediterranean Diet (MD) has been associated with a reduced incidence of neurodegenerative diseases and better cognitive performance. Virgin olive oil, the main source of lipids in the MD, is rich in minor phenolic components, particularly hydroxytyrosol (HT). HT potent antioxidant and anti-inflammatory actions have attracted researchers' attention and may contribute to neuroprotective effects credited to MD. In this review HT bioavailability and pharmacokinetics are presented prior to discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
165
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(176 citation statements)
references
References 126 publications
(157 reference statements)
7
165
0
4
Order By: Relevance
“…This anti-cancer activity of OC was confirmed by several other studies [26][27][28][29]. OC is also associated with a reduced risk of neurodegenerative diseases, such as Alzheimer's disease [30][31][32]. However, nothing is known about the effect of OC in human OA pathology.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…This anti-cancer activity of OC was confirmed by several other studies [26][27][28][29]. OC is also associated with a reduced risk of neurodegenerative diseases, such as Alzheimer's disease [30][31][32]. However, nothing is known about the effect of OC in human OA pathology.…”
Section: Introductionsupporting
confidence: 61%
“…Oleocanthal has attracted considerable attention given its anti-inflammatory, anti-neurodegenerative and anti-cancer activities [20,23,32,[24][25][26][27][28][29][30][31]. Our group demonstrated that OC was able to decrease inflammatory mediators in murine macrophages and mouse chondrogenic cells [23,24], opening the interest to study the potential effect of this phenolic compound in inflammatory degenerative joints diseases, such as OA.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that olive oil may have some anti-inflammatory effects alone. In agreement with our finding, anti-inflammatory effects of olive oil have been demonstrated in other studies (44,45). Olive oil has been used as a vitamin D vehicle in our study.…”
Section: Discussionsupporting
confidence: 82%
“…The role of oxidative stress in development of AD and PD is well established (1) and medicinal herbs with phenolic compound have antioxidant properties are studied as disease-modifying strategies in neurodegenerative diseases. It is proposed that pretreatment with antioxidants can delay neuronal death.…”
Section: Dear Editormentioning
confidence: 99%